Implanted fibroblasts genetically engineered to produce brain-derived neurotrophic factor prevent 1-methyl-4-phenylpyridinium toxicity to dopaminergic neurons in the rat. - Frim, D M (1994)
The trophism of brain-derived neurotrophic factor (BDNF) for dopaminergic cells in culture has led to significant interest in the role of BDNF in the etiology and potential treatment of Parkinson disease. Previous in vivo investigation of BDNF delivery to axotomized substantia nigra dopaminergic neurons in the adult rat has shown no protective effect. In this study, we produced nigral degeneration by infusing 1-methyl-4-phenylpyridinium (MPP+), a mitochondrial complex I inhibitor and the active metabolite of 1-methyl-4-phenyl-1,2,3,6- tetrahydropyridine (MPTP), into the rat striatum. The subsequent loss of nigral neurons was presumably due to mitochondrial toxicity after MPP+ uptake and retrograde transport to the substantia nigra. We engineered immortalized rat fibroblasts to secrete human BDNF and implanted these cells near the substantia nigra 7 days before striatal MPP+ infusion. We found that BDNF-secreting fibroblasts markedly increased nigral dopaminergic neuronal survival when compared to control fibroblast implants. The observation that BDNF prevents MPTP-induced dopaminergic neuronal degeneration in the adult brain has significance for the treatment of neurodegenerative disorders, which may involve mitochondrial dysfunction, such as Parkinson disease.